MENGAKUI DAN MENERIMA KERAGAMAN: Pengalaman Pelajar Islam Belajar di SMA Donbosco - Ashadi, Andri (Turast: Jurnal Penelitian dan Pengabdian, 2014)
Finding Muslim students learn in the schools by run other faiths in an era of democratization it looks as ifnot innocuous because of strong primordial ties regional, cultural, tribal and religious schools into the publicdomain like though. Interestingly, for the academic year 2012/2013 the majority students of high school (SMA)Donbosco Padang are students of Islamic. So interesting to study the factors and their reasons to learn in SMADonbosco and how they recognize and accept the diversity that is rooted primarily on ethnicity and religion.By using the framework of Marx Weber's theory of rationality and social construction theory of Peter L. Berger,combined with the theory of civic pluralism; recognition and representation, the research concluded that thefirst are certain rational considerations why they choice SMA Donbosco. The second, both externalizing andexperience through their objectivization can acknowledge and accept ethnic differences and religious.